Tensile force and bond stress of longitudinal reinforcemenet in heavily reinforced concrete beam - Imran, Nik Farhanim (2011)
This dissertation presents an experimental study related to the tensile force and bond stress of longitudinal reinforcement in heavily reinforced concrete beam. The test variables in this study include the ratio of longitudinal and shear reinforcement. The beam specimens are simply supported with two point load with 130mm wide, 230mm deep and 1800mm long. The tensile force behavior and bond stress of longitudinal reinforcement is observed at support region. From experimental and analytical analysis, all beam specimens are not encounter failure in bond at support region. The beam with higher longitudinal and shear reinforcement ratio experienced lower bond stress compared to the lower longitudinal and shear reinforcement ratio. Besides that, the tensile force at the support is increased significantly after the occurrence of the diagonal cracks. As the reinforcement in the middle beam yield, the tensile force at the support stops increasing. Additionally, a computer program developed to determine the bond stress-slip curve at the support zone by applying Second Order Runge-Kutta method. Bond stress along longitudinal reinforcement beyond the outer part of the support also examined theoretically using local bond stress-slip model that modified from CEB-FIP Model Code 1990.